Reconstructing Legal Rights over MSME Business Premises on State and Waqf Land: A Comparative Legal Study - Ilman Khairi; Nova Monaya; Sudiman Sihotang (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This article reconstructs the legal framework governing proprietary rights over Micro, Small, and Medium Enterprise (MSME) business premises situated on state, regional, and waqf land in Indonesia. The study departs from the persistent legal uncertainty surrounding kiosks and stalls in government-owned traditional markets, particularly the weak proprietary status of SIPTU/SHPTU instruments. In response, the article develops a normative-comparative model of SKBG Tempat Usaha UMKM as a legal mechanism for strengthening the protection of MSME business premises. The proposed model extends the concept of building ownership certificates under the Indonesian Flats Law, particularly the provisions relating to state, regional, and waqf land, from residential units to MSME business premises. Using statutory, conceptual, and comparative legal approaches, this article examines Article 60 of Government Regulation No. 7 of 2021, Article 53A of Law No. 11 of 2020, Government Regulation No. 17 of 2021, and relevant provisions of the Flats Law. Comparative reflections on Pakistan and Turkey further strengthen the argument that public assets and waqf property can be institutionally transformed into inclusive economic infrastructure. The study finds that legal certainty for MSME business premises requires the implementation of the horizontal separation principle between land and buildings, transparent public registration, enforceable proprietary rights, and broader access to financing through fiduciary security or equivalent legal instruments. The novelty of this article lies in its proposal for the doctrinal and institutional expansion of SKBG from a housing-oriented instrument into a legal framework applicable to MSME-oriented development on public and waqf land. This reconstruction is expected to strengthen legal certainty, improve access to financing, and support inclusive and sustainable economic development for MSMEs in Indonesia.